The Synthesis Of Graphene Films Via Graphene Oxide Reduction Using Green Tea - Abdullah, Muhammad Faiq (2013)
In recent years, graphene has emerged as the most promising nanomaterial for various potential applications especially in biomedical field owing to its unique two dimensional (2D) nanostructure and intriguing physicochemical properties. A simple method to produce graphene was developed by reducing graphene oxide (GO) using green tea polyphenol (GTP) in a batch reactor. The aforementioned method was non-detrimental to the environment, cost effective and scalable for high-volume production. The product of the reduction process was referred as reduced GO (RGO). The effects of weight ratio of GTP/GO and reaction temperature on the reduction of GO were examined in details. The ultraviolet-visible (UV-Vis) spectroscopy, Fourier transform infrared (FTIR), thermogravimetric analysis (TGA) and the measurement of zeta potential as well as the electrophoretic mobility reveal that a successful reduction of GO and the preparation of stable RGO dispersion in aqueous media could be attained by performing the reduction reaction of GO with GTP at 90 ºC using a weight ratio of GTP/GO=1. In addition, the UV-Vis spectroscopy and X-ray photoelectron spectroscopy (XPS) analysis show that the RGO prepared using GTP exhibits final position of absorption peak (271 nm) and intensity of sp2 carbon that almost similar to the RGO produced using hydrazine (N2H4) solution. This observation indicates that the effective reduction property of GTP as compared to the N2H4 solution as a standard reducing agent.